Structure and content of the technology of prevention and correction of disturbances of spatial organization of the body of children 6-10 years old with sensory systems deprivation - Kashuba, Vitaliy; Savlyuk, Svitlana (Journal of Education, Health and Sport, 2017)
Topicality is caused by solving of the tasks of implementation the provisions, at the basic level, of the proposed concept, which was associated with the development of technology and its realization in special educational institutions, which was considered as one of the bases of motor activity of children with sensory systems deprivation (SSD) in the process of physical education of the special boarding school. Objectives of the study: to determine the structure and content of the technology of prevention and correction of disturbances of the spatial organization of the body of children 6-10 years old with deprivation of the sensory system in the process of physical education of a special boarding school. Research results. The basis of the theoretical substantiation of the technology of prevention and correction of violations of SOB of children with SSD in the process of motor activity were the basic approaches, general objective, tasks, conditions and principles of APE. In addition, the continuity of pedagogical influences was ensured through the interaction and mutual influence of different forms of occupation in each other in the process of continuous APE, the theoretical substantiation of the methodical foundations of classes organization, the sequence in studying the educational material, the selection of means, methods and methodical techniques for the formation of proper SOB of children taking into account physical condition. Conclusions. The components of the technology of prevention and correction of violations of SOB of children with SSD were: basic approaches, purpose, tasks, complex diagnostics of components of SOB of children with SSD, principles, methods, methodical techniques, conditions of implementation, means, forms, control and criteria of its effectiveness.